SEKOLAH AKSELERASI - Tawil, Tawil (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2010)
Those who are intelligent are seeds, they are assets of the nation worthwhile. That is if they are educated, trained, nurtured, to be a smart intelligent skilled and virtuous it will benefit and accelerate to the prosperity and progress of the nation and state. But otherwise if they do not obtain a positive development it will be futile and even will bring misfortune. They are intelligent possess the ability to think fast to act quickly and precisely, the required education and treatment systems quickly and accurately. One of the educational system is suitable for those who are intelligent educational acceleration or acceleration. There are three systems of education for them is the segregation or separation, enrichment or enrichment, and acceleration or acceleration. System acceleration or velocity or acceleration is to provide education where those who can intelligently learn and master the material quickly in accordance with their capabilities and maturity, and if necessary to jump to the nextgrade. System is often called the system acceleration (acceleration) or also commonly called the system jumping (exceltation). This principle is believed to be effective to accelerate the print quality seeds at a young age, a lot of young born the doctors at the age of 21 years. Calculate only if the incoming elementary students ages 6 years plus 4 years of study in elementary school, junior 2 years, high school 2 years, 3 years S1, S2 2 years, and S3 2 years, then graduated doctorate at the age of 21 years. It may even be further shortened again, it will be born many doctors at a young age. Terbinanya also those who have a particular talent in various areas of life, which in turn can contribute to the acceleration of prosperity and progress of the nation and state. Of course, in addition there is excess accelerated school also has shortcomings, but as long as it is believed many benefits for innovation of education in Indonesia particularly in education services for those who have the intelligenceprivileges.